(untitled) (Quaestiones Disputatae: temas en debate, 2022)
The Juan de Castellanos University Foundation, through the Social Work programme, reflects the disciplinary and missionary sense in its students, and assumes a political character insofar as its social action is based on the community interrelationship that has an impact on the realities of individuals. This is why a pedagogical system of enquiry is proposed based on the radio as a holistic structure that, from its essence, strengthens skills around the participation and cultural intervention of future professionals. The knowledge and reflection of social feeling through the radio become inputs for political construction that reaffirm the critical thinking and experience of the subjects, as well as motivating new perspectives and possible debates on how the political transcends the value and ethical elements that develop the personal, family and social environment; cultural mediation within and outside university life for decision-making and the development of life skills. It is for this reason that the objectives outlined in this experience seek to rethink the need to create strategies based on mass media to strengthen the disciplinary qualities of the social worker in their training structure from the level of participation from the radio programme Culture and Peace from the Juan de Castellanos 105.4 FM radio station, carried out from 2015 until the first semester of 2022 uninterrupted.